Morpholino antisense oligo inhibits trans-splicing of pre-inositol 1, 4, 5-trisphosphate receptor mRNA of Trypanosoma cruzi and suppresses parasite growth and infectivity. Issue 3 (June 2016) - Hashimoto, Muneaki; Nara, Takeshi; Mita, Toshihiro; Mikoshiba, Katsuhiko
Abstract: Morpholino antisense oligos (MAOs) are used to investigate physiological gene function by inhibiting gene translation or construction of specific alternative splicing variants by blocking cis -splicing. MAOs are attractive drug candidates for viral- and bacterial-infectious disease therapy because of properties such as in vivo stability and specificity to target genes. Recently, we showed that phosphorothioate antisense oligos against Trypanosoma cruzi inositol 1, 4, 5-trisphosphate receptor ( TcIP 3 R ) mRNA inhibit the parasite host cell infection. In the present study, we identified the spliced leader (SL) acceptor of pre- TcIP 3 R mRNA and synthesized MAO, which inhibited trans -splicing of the transcript (MAO-1). MAO-1 was found to inhibit the addition of SL-RNA to pre- TcIP 3 R mRNA by real-time RT-PCR analysis. Treatment of the parasites with MAO-1 significantly impaired the growth and infectivity into host cells. These results indicate that MAO-1 is a potential novel drug for Chagas disease and that MAOs inhibiting trans -splicing can be used to investigate the physiology of trypanosomal genes leading to the development of novel drugs. Graphical abstract: Highlights: We identified the SL acceptor of pre- TcIP 3 R mRNA. We designed a morpholino antisense oligo to inhibit TcIP 3 R mRNA maturation. Antisense oligo inhibits T. cruzi epimastigote growth and trypomastigote infectivity. Morpholino antisense oligo is a potential novel drug. Trans -splicing inhibition could be a good target drug for trypanosomiasis.